2011
DOI: 10.4238/2011.december.14.10
|View full text |Cite
|
Sign up to set email alerts
|

Key pathways involved in prostate cancer based on gene set enrichment analysis and meta analysis

Abstract: ABSTRACT. Prostate cancer is one of the most common male malignant neoplasms; however, its causes are not completely understood. A few recent studies have used gene expression profiling of prostate cancer to identify differentially expressed genes and possible relevant pathways. However, few studies have examined the genetic mechanics of prostate cancer at the pathway level to search for such pathways. We used gene set enrichment analysis and a meta-analysis of six independent studies after standardized microa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 36 publications
0
14
0
Order By: Relevance
“…Although the potential association of the RTK/ERK pathway with prostate cancer risk has been suggested by our previous study 1012 , the genetic and functional link of the pathway to aggressive prostate cancer have not been elucidated. In this work, on the basis of the Chinese Consortium for Prostate Cancer Genetics (ChinaPCa) project, we performed SNP- and gene-based prostate cancer case-only study, as well as expression quantitative trait loci (eQTL), clinical correlation, and prognosis analyses.…”
Section: Introductionmentioning
confidence: 83%
See 1 more Smart Citation
“…Although the potential association of the RTK/ERK pathway with prostate cancer risk has been suggested by our previous study 1012 , the genetic and functional link of the pathway to aggressive prostate cancer have not been elucidated. In this work, on the basis of the Chinese Consortium for Prostate Cancer Genetics (ChinaPCa) project, we performed SNP- and gene-based prostate cancer case-only study, as well as expression quantitative trait loci (eQTL), clinical correlation, and prognosis analyses.…”
Section: Introductionmentioning
confidence: 83%
“…In addition, considerable evidence indicated that the signaling pathways including AR, PI3K/AKT, and RTK/ERK 79 have been identified as the key factors for prostate cancer risk, yet the underlying genetic basis remains elusive. The association analyses in our previous work suggested that the RTK/ERK pathway might be a significant factor conferring risk of prostate cancer 1012 . Moreover, recent studies demonstrated the important role of this pathway in metastasis and progression of prostate cancer 13, 14 .…”
Section: Introductionmentioning
confidence: 90%
“…Finally, 3 groups of data, including HNF1b co-expression genes from GEO, prostate cancer genes from DDPC, and meta-analysis of 6 independent gene expression profiling studies about prostate cancer (Ning et al, 2011), were checked manually to identify genes that were themselves not only related to HNF1b but also associated with prostate cancer susceptibility.…”
Section: Genes Implicated In Ddpcmentioning
confidence: 99%
“…To address the hypothesis, we applied the microarray datasets from Gene Expression Omnibus (GEO) to generate genes whose expression is significantly correlated with HNF1b. The HNF1b-correlated genes were then compared with genes reported to be implicated in prostate cancer by Dragon Database (DDPC; http://apps.sanbi.ac.za/ddpc/) and our previous meta-analysis of 6 independent gene expression profiling studies about prostate cancer from GEO (Ning et al, 2011). Thus, HNF1b-associated prostate cancer genes were obtained.…”
Section: Introductionmentioning
confidence: 99%
“…Specifically, Ago2, the co-target of miRNA-145, miR-184 and miR-802, played an important role in GC differentiation, lymph node invasion and clinical stage [33]. Myc, a multiplayer in carcinogenesis, progression and metabolism, was also the predicted target of miR-145 and miR-184 [34]. Moreover, many target genes related to VEGF receptor signaling pathway have been identified, such as VEGFR-3.…”
Section: Discussionmentioning
confidence: 99%